Current application of tissue-engineered dermal scaffolds mimicking the extracellular matrix microenvironment in wound healing - Xinran Ding; Sujie Xie; Wei Zhang; Yushu Zhu; Dayuan Xu; Shuyuan Xian; Hanlin Sun; Xinya Guo; Yixu Li; Jianyu Lu; Xirui Tong; Runzhi Huang; et al. (Regenerative Therapy, 2025)
With the continuous advancement of materials science, cell biology, and biotechnology, tissue engineering has introduced novel solutions to traditional wound healing approaches, particularly demonstrating significant potential in addressing complex or non-healing wounds. One of the key technologies in this field, dermal scaffolds, serve as wound coverage materials that mimic the structural framework of the dermis. They primarily assume the function of extracellular matrix, providing space for cell attachment, migration, and proliferation, thus supporting cellular growth and regulating multiple biological processes in healing. Tissue engineering utilizes combinations of natural or synthetic scaffolds, seeded cells, or growth factors to induce distinct effects in angiogenesis, extracellular matrix deposition, and functional recovery. Therefore, various bioengineered dermal scaffolds hold significant potential for clinical translation in wound healing. This review outlines various extracellular matrix molecules utilized in the development of dermal scaffolds, emphasizes recent progress in cell- and growth factor-modified scaffolds, and discusses the challenges and future perspectives in this evolving field.